193k views
7 votes
Multiply: (-5qr) × (-2pqr) × pq​

User Sali
by
5.0k points

1 Answer

0 votes

Answer:

The product of (-5·q·r) × (-2·p·q·r) × p·q is 10·q³·r²·p²

Explanation:

The question relates to the rules of multiplication of variables and indices rules, and simplifification of an expression ;

The given expression is (-5·q·r) × (-2·p·q·r) × p·q

Therefore, we have;

(-5·q·r) × (-2·p·q·r) × p·q = (-5) × (-2) × q×q×q × r×r ×p×p = 10 × q³ × r² × p²

10 × q³ × r² × p² = 10·q³·r²·p²

∴ (-5·q·r) × (-2·p·q·r) × p·q = 10 × q³ × r² × p² = 10·q³·r²·p²

(-5·q·r) × (-2·p·q·r) × p·q = 10·q³·r²·p².

User Butaminas
by
5.4k points